Cellular senescence in osteoarthritis and anti-aging strategies. (October 2018) - Hou, Angyang; Chen, Peng; Tang, He; Meng, Haoye; Cheng, Xiaoqing; Wang, Yu; Zhang, Yuming; Peng, Jiang
Highlights: We introduced a variety of studies on the problem of cell senescence in osteoarthritis in recent years. Some anti-aging treatment methods for osteoarthritis are reviewed, and new ideas and directions are provided for the treatment of osteoarthritis. Our review may provide some insights into other age-related diseases. Abstract: In older adults, the prevalence of osteoarthritis (OA) increases directly with age and is the most common cause of chronic disability. It is necessary to recognize that OA is a degenerative disease that strongly correlates with age, and often promotes elevated levels of cartilage injury. Chondrocytes undergo an age-dependent decline in proliferative and synthetic capacity. It is thought that cellular senescence may play a significant role in the pathology of OA, with chondrocytes exhibiting a variety of senescence-associated phenotypes. In this review, we discuss cellular senescence and its relationship with OA. More importantly, we introduce novel strategies for the modulation of cellular senescence, including the use of sirtuin 6, mammalian target of rapamycin, N-acetyl-l -cysteine, proteoglycan-4 and senolytic, which may help to delay senescence and improve cartilage regeneration in the aging population.